French Silver in the J. Paul Getty Museum - Bremer-David, Charissa (J. Paul Getty Trust, 2023)
Vividly illustrated, this is the first comprehensive catalogue of the J. Paul Getty Museum's celebrated collection of seventeenth- and eighteenth-century French silver. The collection of seventeenth- and eighteenth-century French silver at the J. Paul Getty Museum is of exceptional quality and state of preservation. Each piece is remarkable for its beauty, inventive form, skillful execution, illustrious provenance, and the renown of its maker. This volume is the first complete study of these exquisite objects, with more than 250 color photographs bringing into focus extraordinary details such as minuscule makers' marks, inscriptions, and heraldic armorials. The publication details the formation of the Museum's collection of French silver, several pieces of which were selected by J. Paul Getty himself, and discusses the regulations of the historic Parisian guild of gold- and silversmiths that set quality controls and consumer protections. Comprehensive entries catalogue a total of thirty-three pieces with descriptions, provenance, exhibition history, and technical information. The related commentaries shed light on the function of these objects and the roles they played in the daily lives of their prosperous owners. The book also includes maker biographies and a full bibliography. The free online edition of this open-access publication is available at getty.edu/publications/french-silver/ and includes 360-degree views and zoomable high-resolution photography. Also available are free PDF and EPUB downloads of the book, and JPG downloads of the main catalogue images.